汉柬第一人称代词对比研究 - MENG POLY (Journal International Lingua Mandarin (JILIN), 2023)
[摘要] 人称代词在日常交际中起着至关重要的作用。汉语和柬埔寨语第一人称代词既有相同点，也有不同点。文章对比分析了汉语和柬埔寨语第一人称代词，发现其相同点在于，汉语第一人称代词是不区分男女性别的，部分柬埔寨语第一人称代词也是不区分男女性别的，共有9个。不同点在于，柬埔寨语中的第一人称代词远多于汉语第一人称代词，共有21个。汉语中第一人称代词只有一种复数形式，即在“我”、“咱”后面加上“们”，而柬埔寨语中则有三种形式；汉语第一人称代词“我”、“我们”、“咱”、“咱们”使用起来都比较简单，而柬埔寨语中第一人称代词使用起来则比较复杂，柬埔寨语第一人称代词会随着感情色彩、礼貌程度和关系的亲疏远近的转变而转变，在实际使用中需要注意对话双方的年龄、辈分、社会地位等特点选择不同的人称代词。[Abstract] Personal Pronouns play a crucial role in everyday communication.Chinese and Cambodian first person pronouns have both similarities and differences.The article compares and analyzes the first person pronouns in Chinese and Cambodian and finds that the similarities are that the first person pronouns in Chinese are gender-neutral, while some of the first person pronouns in Cambodian are also gender-neutral, with 9 in total.The difference is that there are far more Cambodian first person pronouns than Chinese first person pronouns, 21 in total.In Chinese, there is only one plural form of first person pronouns, while there are three forms in Cambodian; The Chinese first person pronouns "wo", "wo men", "zan" and "zan men" are all relatively simple to use, while the Cambodian first person pronouns are relatively complex to use.The first person pronouns in Cambodian will change with the change of emotional color, politeness and relationship.In actual use, it is necessary to pay attention to the age, generation, social status and other characteristics of the two sides of the conversation to choose different personal pronouns.